2022
DOI: 10.1111/luts.12443
|View full text |Cite
|
Sign up to set email alerts
|

Do we have enough evidence to propose a urinary biomarker of bladder ischemia? A systematic review and meta‐analysis

Abstract: Objective Urinary bladder ischemia has been implicated in the pathogenesis of lower urinary tract symptoms (LUTS). However, research regarding urinary molecular markers for diagnosis and prognosis of pelvic ischemia is still premature, hindering further implementation in clinical practice. The aim of this study is to systematically appraise biomarkers associated with bladder ischemia detected in urine. Methods We performed a systematic review of PubMed/Medline, Embase, Web of Science, and the Cochrane Library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“… 15 A systematic review and meta-analysis revealed that 8-hydroxy-2’-deoxyguanosine (8-OHdG) plays an essential role in the diagnosis and prognosis of lower urinary tract symptoms (LUTS) in patients with vascular injury or bladder outlet obstruction as a urinary biomarker. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 A systematic review and meta-analysis revealed that 8-hydroxy-2’-deoxyguanosine (8-OHdG) plays an essential role in the diagnosis and prognosis of lower urinary tract symptoms (LUTS) in patients with vascular injury or bladder outlet obstruction as a urinary biomarker. 16 …”
Section: Discussionmentioning
confidence: 99%
“…15 A systematic review and meta-analysis revealed that 8-hydroxy-2'-deoxyguanosine (8-OHdG) plays an essential role in the diagnosis and prognosis of lower urinary tract symptoms (LUTS) in patients with vascular injury or bladder outlet obstruction as a urinary biomarker. 16 Zhao et al investigated the free ferrous protoporphyrin and reactive oxygen species (FH and ROS) status to evaluate the relationship between pathological stage and grade of Urothelial Carcinoma for the first time. 11 The combined test aims to evaluate the prognosis and formulate further treatment plans.…”
mentioning
confidence: 99%
“…Many professional, social, and personal problems as well as difficult situations are caused or aggravated by stress. Labor productivity decreases significantly under conditions of stress [5], depression, and some psychogenic and pathological diseases as well as in the sexual ability of both men and women [6].…”
Section: Introductionmentioning
confidence: 99%